Adsorption of polycyclic aromatic hydrocarbons (PAHs) from aqueous solutions on different sorbents = Adsorpcja wielopierścieniowych węglowodorów aromatycznych (WWA) z roztworów wodnych na różnych sorbentach - Smol, Marzena; Włodarczyk-Makuła, Maria; Włóka, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the results of the possibility and effectiveness of PAHs removal from a model aqueous solution, during the sorption on the selected sorbents. Six PAHs (naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene) listed by EPA for the analysis in the environmental samples were determined. Model aqueous solution was prepared with RESTEK 610 mix PAHs standard.
Keywords: wielopierścieniowe węglowodory aromatyczne (WWA); adsorbcja; piasek kwarcowy; sorbent mineralny; węgiel aktywny; polycyclic aromatic hydrocarbons (PAHs); adsorption; quartz sand; mineral sorbents; activated carbon